Implementación de una contabilidad de costos en la empresa injaulas s.a. ubicada en el cantón Salcedo, provincia de Cotopaxi para el año 2014 - Lascano Salazar, Victoria del Carmen (2015)
This research has been carried out in order to determine the actual cost involved in the production of plastic cages to transport chickens in the Injaulas S.A. Industry, Taking into account the activities in each of the processes. The research was conducted using inductive, deductive and analytical methods as well as statistical, the technique used to compile the information was the interview, it was directed to the manager of the industry in order to know the strengths and weaknesses of it, the survey applied to workers and customers helped to confirm the production management to facilitate the decision-making….